ANALISIS KESULITAN MENULIS RINGKASAN BACAAN PADA TEMA 8 SUBTEMA 2 SISWA KELAS IV MADRASAH IBTIDAIYAH - Shofaul Hikmah (INOPENDAS: Jurnal Ilmiah Kependidikan, 2022)
The problem that is often encountered in learning Indonesian at the basic level is the ability to write. One of the difficulties faced by class IVB MIN 1 Rembang students is the difficulty in writing summary readings. This study aims to determine the difficulty of writing a summary and to find out the factors causing the difficulty of writing a summary in class IVB MIN 1 Rembang. This research is a qualitative descriptive research with case study method. Data collection techniques by means of observation, interviews and document analysis. Data analysis techniques from data reduction, data presentation and verification. The results showed that there were difficulties experienced by students in writing summaries, namely, lack of understanding difficult vocabulary, difficulties in writing what they thought in written form and understanding long readings. The causative factor is the students' internal and external factors. Internal factors include difficulty concentrating during learning, boredom while studying and lack of understanding of the material. External factors, namely, teaching methods and learning media.